The Relationship between Diet and Physical Activity and Blood Pressure in Adolescents - Muhammad Zaky Ikhsani; Sofiana Nurchayati; Siti Rahmalia Hairani Damanik (Journal of Education Technology Information Social Sciences and Health, 2024)
The prevalence of hypertension in adolescents in Indonesia shows a very rapid increase. This is a common blood pressure problem. This can be caused by unhealthy eating patterns and lack of exercise. This study aims to determine the relationship between diet and physical activity levels with blood pressure in adolescents. This research uses a correlational analytical research design with a cross sectional approach. The sample in this study was 116 students in grades 10, 11 and 12 of SMAN 2 Dumai City. The collected data was analyzed univariately and bivariately using the chi square test. The results of univariate analysis showed that the majority of respondents were in their middle teens, 83 people (71.6%), 80 people (69.0%) were female, 114 people (98.3%) did not smoke, 79 people (68%) had normal systolic blood pressure. .1%), normal diastolic blood pressure in 81 people (69.8%), good diet in 80 people (69.0%), and heavy physical activity in 90 people (77.6%). Based on the results of the chi square test, significant values were obtained for the systolic diet variable with a value of ρ 0.000 α 0.05, and the diastolic diet variable with a value of ρ 0.000 α 0.05 and the systolic physical activity variable with a value of ρ 0.204 α 0.05 and physical activity in diastole with a value of ρ 0.231 α 0.05. It can be concluded that there is a relationship between diet and blood pressure in adolescents, and there is no relationship between physical activity and hypertension blood pressure in adolescents.